A novel design of circularly polarized pentagonal planar antenna for ISM band applications - F. Ouberri; A. Tajmouati; J. Zbitou; I. Zahraoui; M. Latrach (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
This paper presents a new circular polarized micro-strip antenna with a pentagonal shape radiator. The proposed antenna is designed to operate in the industrial scientific medical (ISM) band at the frequency of 2.45GHz for Wireless applications. The antenna consists of a radiating pentagon patch with appropriate dimensions on the upper side of a dielectric substrate and a defective ground structure (DGS) on the other side. The pentagon patch is fed through a 50Ω microstrip line. The structure is implemented on an FR-4 substrate with a relative permittivity of 4.4, loss tangent equal to 0.025 and thickness 1.58 mm. The antenna is designed and simulated by using advanced design system (ADS) electromagnetic solver and the achieved results are validated by using another electromagnetic solver. The simulation results indicate that the designed circularly polarized (CP) pentagonal microstrip patch antenna gives good results in terms of the reflection coefficient, voltage standing wave ratio (VSWR) and, axial ratio of 1.025 at 2.45 GHz.